Влияние содержания ультрадисперсных алмазов на свойства композитов на основе ароматического полиамида - Буря, А.И.; Шерстюк, А.И.; Иващенко, В.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
With the aim of expanding the range of fillers improving APA properties, we have chosen superdispersed diamonds (SDD) which combine high stability, hardness, good electricity and heat conductivity, on the one hand, and the developed chemically active surface of circular particles, on
the other hand. SDD (4 – 6 nm) in the amount of 0.2, 0.5, 1.0 mass % were introduced into APA phenilon С-
2 within the rotating electromagnetic field with the help of ferromagnetic particles which were later
removed from the prepared composition by means of mechanic separation.
As the testing results have shown, the concentration dependence of the elaborated nanocomposites reaches its maximum at SDD content of 0.5 mass %. At the optimum filler content the yield strength and the coefficient of elasticity at compression reach the values of 232.3 (225.9 for phenilon) and 2926.9 (2822.4) МPа correspondingly.